Google sites como herramienta didáctica en el proceso de enseñanza-aprendizaje de Biología Humana con estudiantes de sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Remache Yucailla, Nilver Danilo (2024)
The digital world is integrated into the educational context, allowing the generation of dynamic and interactive learning environments during the study of Human Biology. The problem was evidenced by the limited use of digital resources for the creation of interactive didactic content that allows the active participation of the student. The objective was to propose the use of Google sites as a didactic tool in the teaching-learning process of the subject of Human Biology of the career of Pedagogy of Experimental Sciences, Chemistry and Biology. The methodology was quantitative, non-experimental, at a descriptive level, due to the bibliographic place, in the field, finally analysis-synthesis methods were used. For data collection, the survey was used as a technique and the questionnaire was applied to 13 sixth-semester students. After analyzing the results obtained, it was concluded that the proposal of using Google sites as a didactic tool is totally favorable, this finding shows that Google sites is a beneficial tool for the learning process of Human Biology, since it allows the design and organization of didactic contents, such as the interactive guide "Knowing the Human Body" A resource that awakens motivation, encourages the active participation of students, helping to achieve significant learning, useful in the educational context. Therefore, it is recommended to make use of interactive didactic guides, as a support for the teaching and learning of Human Biology.